Fatores associados aos desfechos desfavoráveis de tuberculose em idosos no Brasil: análise multinomial - Rodrigues, Leticia do Nascimento (2023)
Introduction: Tuberculosis (TB), despite being a treatable and curable ancient disease, still represents a significant public health problem globally. Among the groups with higher vulnerability to developing TB are the elderly, who have a higher mortality rate compared to non-elderly individuals. Objective: To identify, within the three vulnerability axes, the factors associated with unfavorable outcomes of loss to follow-up, TB-related death, and death from other causes among the elderly in Brazil during the period from 2015 to 2019. Methods: This is a cross-sectional study using secondary data from the Notifiable Diseases Information System (SINAN) of TB cases reported between January 1, 2015, and December 31, 2019, in people aged 60 years or older. The dependent variable was the treatment outcome, and co-variables associated with the outcome of interest (p ≤ 0.20) were included in a multinomial logistic regression model, using the cure category as the reference. Results: Elderly individuals who self-identified as Black and Brown, were homeless, had mental health disorders, lived with HIV, and used licit and illicit drugs had a higher likelihood of treatment loss to follow-up. Meanwhile, elderly individuals who were homeless, had mental health disorders, used licit and illicit drugs, and did not undergo bacilloscopy had higher chances of death due to TB. For the outcome of death from other causes, individuals living with diabetes mellitus (DM) and HIV, and those using licit and illicit drugs had higher chances of this outcome. On the other hand, those living with DM and those with positive bacilloscopy results had lower chances of treatment loss to follow-up. Those with higher levels of education and those who did not undergo bacilloscopy had lower chances of death from other causes. Also, individuals with higher levels of education had lower chances of death from TB. Conclusion:The results of this study indicate that characteristics related to vulnerability are significantly associated with unfavorable tuberculosis outcomes in the elderly. Finally, specific strategies and a comprehensive approach, considering medical, social, and psychosocial aspects, are crucial to address the complex challenges related to tuberculosis and achieve better treatment outcomes for TB in the elderly and the occurrence of a favorable outcome.